Ag-Data Hub: Cultivating Innovation, Harvesting Insights, Growing a Sustainable Future - Wilson, Michael; Tepa-Yotto, Ghislain; Dalaa, Mustapha; Martey, Francisca; Yeboah, Stephen; Awotwi, John; Danquah, Paul (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Ghana Digital Agricultural Data Hub (Ag-Data Hub) has the ultimate goal of becoming the go-to national platform for digital data exchange and to serve as a backbone for information and data sharing among stakeholders and for the development of fact-based decision support systems to drive policy-making and to trigger a move towards sustainable climate smart agricultural practices. Detailed information on the implementation steps that were followed is available at https://poc.miphost.com/ . In 2023, the Ag-Data hub transitioned from the planning phase to an implementation phase. The year ended with a Minimum Viable Product(MVP) of the hub that is currently undergoing final User Acceptance Testing for Go-Live. The current MVP is accessible at http://ghanaaghub.com/ . This document outlines and discusses key lessons learnt during the implementation phase of the Ag-Data Hub. We also discuss a high-level overview of our Go-Live plan and how we intend to scale from our current test servers to production servers to serve the nation.